The complement control-related genes CSMD1 and CSMD2 associate to schizophrenia - Håvik, Bjarte; Le Hellard, Stephanie; Rietschel, Marcella; Lybæk, Helle; Djurovic, Srdjan; Mattheisen, Manuel; Mühleisen, Thomas W.; Degenhardt, Franziska; Priebe, Lutz; Maier, Wolfgang; Breuer, René; Schulze, Thomas G.; et al. (Biological psychiatry, 2011)
Background - Patients with schizophrenia often suffer from cognitive dysfunction, including impaired learning and memory. We recently demonstrated that long-term potentiation in rat hippocampus, a mechanistic model of learning and memory, is linked to gene expression changes in immunity-related processes involved in complement activity and antigen presentation. We therefore aimed to examine whether key regulators of these processes are genetic susceptibility factors in schizophrenia. - Methods - Analysis of genetic association was based on data mining of genotypes from a German genome-wide association study and a multiplex GoldenGate tag single nucleotide polymorphism (SNP)-based assay of Norwegian and Danish case-control samples (Scandinavian Collaboration on Psychiatric Etiology), including 1133 patients with schizophrenia and 2444 healthy control subjects. - Results - Allelic associations were found across all three samples for eight common SNPs in the complement control-related gene CSMD2 (CUB and Sushi Multiple Domains 2) on chromosome 1p35.1-34.3, of which rs911213 reached a statistical significance comparable to that of a genome wide threshold (p value = 4.0 × 10−8; odd ratio = .73, 95% confidence interval = .65-.82). The second most significant gene was CSMD1 on chromosome 8p23.2, a homologue to CSMD2. In addition, we observed replicated associations in the complement surface receptor CD46 as well as the major histocompatibility complex genes HLA-DMB and HLA-DOA. - Conclusions - These data demonstrate a significant role of complement control-related genes in the etiology of schizophrenia and support disease mechanisms that involve the activity of immunity-related pathways in the brain.
Gesehen am 23.09.2022